DECONSTRUCTIVE ANALYSIS OF MAIN CHARACTER IN FRANKENSTEIN NOVEL BY MERY SHELLEY - Femilia Bowta; Yulan Puluhulawa (British (Jurnal Bahasa dan Sastra Inggris), 2018)
The purpose of this research is to deconstruct the main character of  Frankenstein novel. This is qualitative research with deconstructive approach. Deconstruction is a method of reading texts which shows that in every text there is always an absolute presumption. Deconstruction is used to find other meanings hidden in a text. The steps taken by the writer in deconstructing Frankenstein's novel are describing Victor's character, finding binary opposition in the character then deconstructing Victor's character. The results are the portrayal of Victor after deconstruction that Victor himself was the cause of all the chaos done by his creatures.  Victor's ambitions that are too deep in science make him a different person, from a good character to very selfish and cruel.Keywords: Deconstructive, Main Character, Binary Opposition, Frankenstein Novel